The Effect of Show and Tell Toward Students’ Speaking Skill at The Eighth Grade Students of Islamic Junior High School Darul Ulum West Jakarta in Academic Year 2021/2022 - Gunadiputra, Ilhamy Ilyas; Gumelar, Rizdki Elang; Sari, Raisa Rahmi (Universitas Mathla'ul Anwar Banten, 2022)
This study aims to investigate the effect of Show and Tell Toward Students’ Speaking Skill at The Eighth Grade Students of Islamic Junior High School Darul Ulum West Jakarta in Academic Year 2021/2022. This study used quantitative approach with quasi experimental method using pre-test post-test control and experimental group design. In this research the researcher used cluster random sampling technique with total of sample is 60 students. In order to analyze the data, the researcher used statistical computation by using SPSS software. After conducting the research by giving pre-test and post-test to experimental class by using show and tell and storytelling in control class, the researcher calculate the pre-requirement of research analysis (normality and homogeneity test). The result of normality test shows that p-value (0.069, 0.066, 0.062, and 0.086) are higher than α = 0.05, on the other word the data is normally distributed, while the result of homogeneity test shows that p-value of Pre-Test is (0,756) > α = 0.05 and p-value Post-Test is (0,288)> α = 0.05, on the other word, the data are homogenous. The last step is calculating the t-test, the kind of t-test used is Paired Sample T-test. The result shows that sig. (2-tailed) = 0.000 < 0.05, it means that Show and Tell has significant effect to increasing students’ speaking skill.